Heart of darkness and other tales - Conrad, Joseph, 1857-1924 (Oxford University Press, 1990)
Set in an atmosphere of mystery and menace, "Heat of Darkness" tells the story of Marlow's journey up the Congo River to meet the remarkable Mr. Kurtz. It reveals Conrad at the height of his powers as a writer of great vividness, intensity, and sophistication. "An Outpost of Progress" is also set in central Africa and offers a fiercely sardonic view of European imperialism. "Karain", with its Malaysian setting, questions conventional ideas of the contrasts between races. "Youth" is a largely autobiographical account of an inn-fated voyage in which Marlow